A GENEALOGY FOR 'COST OR MARKET' - Littleton, A. C. (The Accounting Review, 1941)
Several surveys of inventory practices have been made. The N.A.C.A. Bulletin of March, 1937, showed that 87% of 197 companies used the rule of cost or market whichever is lower for raw materials in their balance sheets. A report of February 1938 by the National Industrial Conference Board analyzed 916 companies. The rule was applied to raw materials in 63% of the cases, to goods in process in 38% and to furnished goods in 40% of the cases. The research department of the American Institute of Accountants examined 500 annual reports for 1939. The figures tabulated in The Journal of Accountancy for October 1940 show that 56% followed this rule "or variations thereof." These surveys as samples of practice show that the rule is in general use. But a rule may be widely useful in business without having the character necessary to make it a fundamental proposition of accounting. If we wish to search out the character of this rule, if we would like to determine whether it is a convenient and expedient rule of thumb or a basic accounting idea, we might begin by looking up its ancestry.